Approaches Of Arabic Education Research: Criticism And New Offers Of Methodology Diversification - Maimun, Agus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Research of Arabic Education (AE) is a systematic investigation of interesting research questions about the Arabic language. Arabic Education Research can use a variety of approaches, types, and designs. For this reason, diversification of research methodology is needed so that it is not concentrated in certain research approaches and types. This study aims to describe: (1) the approach and type of research used by students in thesis research; (2) mastery of scientific substance and research methodology of students; (3) weaknesses that occur in student thesis writing. This research is descriptive-quantitative. Data collected by documents and interviews. Data were analyzed with percentages and reflective thinking. The results showed that: (1) most students conducted research using a quantitative approach, with the type of experimentation, and quasi-experiment design, (2) the substance and methodology of the students showed good mastery, and (3) weaknesses that occurred in student thesis writing lies in the weakness in making research abstracts and discussing research results. For this reason, it is suggested the need to increase students' insights in the field of research methodology, so that student research is not focused on specific approaches and types of research, so that it spreads to all approaches and types of research. However, the choice of approach and type of research must still adjust to the scientific characteristics and the problem under study.